Pengaturan Inkonstitusional Bersyarat pada Kewenangan Pengujian Formil Undang–Undang terhadap Undang-Undang Dasar - Meri Yarni; Khofifah Rizki Amanda (Jurnal Konstitusi, 2024)
The purpose of this research is to examine and analyze the Conditional Unconstitutionality Provisions in the authority of formal review of laws against the 1945 Constitution of Indonesia. This study analyzes the legal legitimacy of the Constitutional Court’s conditional unconstitutional decisions, specifically Decision Number 91/PUU-XVIII/2020 concerning the Job Creation Law, and the Ius Constituendum of Conditional Unconstitutionality in the context of formal review for law examination. A normative juridical research method with qualitative descriptive analysis was employed. The findings reveal that the legal force of conditional unconstitutional decisions is binding and mandatory, recommending the revision of laws to clarify the scope and legal standing of conditional unconstitutional decisions, ensure compliance with constitutional mandates, and support the principle of checks and balances. The Ius Constituendum in the Constitutional Court’s decisions emphasizes the improvement of relevant laws and collaboration among state institutions. The author’s recommendations include the establishment of a legal basis through the revision of the Constitutional Court Law to incorporate conditional decisions as a foundation for implementing the constitutional judiciary’s authority.